2019
DOI: 10.1080/10447318.2019.1572353
|View full text |Cite
|
Sign up to set email alerts
|

In Automatic We Trust: Investigating the Impact of Trust, Control, Personality Characteristics, and Extrinsic and Intrinsic Motivations on the Acceptance of Autonomous Vehicles

Abstract: According to industry research, the automation of vehicles promises a revolution in traffic safety, mobility, and quality of life. However, the success of such vehicles depends on their acceptance. This study investigates the influence of trust in technology, concerns of giving up control, perceived usefulness, perceived ease of use, the personality factor innovativeness, and the enjoyment of driving a car on the a priori intention to adopt an autonomous vehicle. By means of an online survey with 369 German pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(82 citation statements)
references
References 108 publications
5
69
1
Order By: Relevance
“…[66,67]) our study supported the positive effect of perceived usefulness on the behavioral intention to use both AVs. Contrary to Hein et al [68] as well as Lee et al [4] and Hegner et al [69] and, similarly to Xu et al [29], we found impact of perceived ease of use on the behavioral intention to use AVs, but in our experiment this effect was mediated by the perceived usefulness in both conditions. While Choi and Ji [48] reported that perceived ease of use did not influence the perceived usefulness, our findings show the contrary.…”
Section: Theoretical Contributioncontrasting
confidence: 96%
See 2 more Smart Citations
“…[66,67]) our study supported the positive effect of perceived usefulness on the behavioral intention to use both AVs. Contrary to Hein et al [68] as well as Lee et al [4] and Hegner et al [69] and, similarly to Xu et al [29], we found impact of perceived ease of use on the behavioral intention to use AVs, but in our experiment this effect was mediated by the perceived usefulness in both conditions. While Choi and Ji [48] reported that perceived ease of use did not influence the perceived usefulness, our findings show the contrary.…”
Section: Theoretical Contributioncontrasting
confidence: 96%
“…Moreover, Choi and Ji [48] reported that perceived ease of use did not influence the perceived usefulness, while both those factors positively impacted intention to use AVs. Moreover, Hein et al [68] as well as Lee et al [4] and Hegner et al [69] showed that the perceived ease of use did not influence the intention to use (contrary to the effect of perceived usefulness), while it influenced positively perceived usefulness and intention to use. Interestingly, in the case of level 3 AVs, it was reported that it was the ease of use which predicted the intention to use and not perceived usefulness [30].…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Malle et al [68,92] have identified four main dimensions of trust in robots (reliable, capable, ethical, and sincere), which they argue can be further grouped into two main dimensions; capacity trust (reliable, capable) and moral trust (ethical, sincere). To a certain degree, trust in a (social) robot's capacity is akin to trust in other types of autonomous intelligent devices, such as autonomous cars [38,56]. However, in such devices social trust typically does not play a role, unlike with social robots, where interpersonal elements begin to be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last couple of years, ADVs have only been discussed as a conceptual idea. Despite the fact that several researchers have investigated the acceptance of autonomous vehicles (AVs) in general (e.g., autonomous cars and shuttles) ( Hohenberger et al, 2016 , Panagiotopoulos and Dimitrakopoulos, 2018 , Hegner et al, 2019 ), very little is known about the acceptance of ADVs (Kapser and Abdelrahman, 2020b, 2019, 2020a; Marsden et al, 2018 , Pani et al, 2020 ). To get a more comprehensive overview of the constructs determining user acceptance of ADVs, within this study a modified UTAUT2 model, which has been verified in previous research is adopted and extended with additional important constructs based on a systematic literature review ( Kapser and Abdelrahman, 2019 , 2020b).…”
Section: Introductionmentioning
confidence: 99%